Physicochemical and functional properties of potato protein isolates and altered foaming properties via forming Maillard conjugates : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Auckland, New Zealand - Zhang, Xin (Massey University, 2019)
Potato protein is a vegetable protein which is currently available commercially as a food protein ingredient. In spite of this fact, potato protein has not been relatively well investigated compared to other plant proteins such as soybean proteins. Therefore, the aim of this study was to investigate the physicochemical and functional properties of potato proteins and their altered functional properties after forming Maillard conjugates using two different types of commercially available potato protein isolates (PPIs) referred to as S200 and S300 in order to gain a better understanding of their use and application in foods. Initially, the effects of some environmental conditions, such as pH (2-12), ionic strength (NaCl 100-1000 mM and CaCl₂ 50-600 mM) and thermal treatment (60, 70, 80, 90 or 100℃ for 1 hour) on the physicochemical properties (e.g. protein solubility, zeta potential and colour) of each PPI in a solution were analysed. Besides, the foaming and emulsifying properties of each PPI solution were also investigated by measuring foaming capacity (FC) and foam stability (FS). Then, the emulsifying properties of PPIs were studied by preparing oil-in-water emulsions using a two-stage high-pressure homogenizer and changing the composition of emulsions (10, 15 and 20% oil and 1 and 3% protein). The properties and stability of potato protein emulsions were analysed by measuring the zeta potential, particle size and microscopic examination (CLSM) of emulsion oil droplets. The emulsions containing 1% PPI and 10% oil were also characterised further for their stability by altering the pH of emulsions and adding salts (NaCl and CaCl2) at different concentrations as well as applying thermal treatment and freezing-thawing. Apart from the above, the two PPIs and some selected polysaccharides, including maltodextrin (MD), pectin and sodium alginate (SA), were used to prepare Maillard conjugates to investigate whether the functional property (i.e. foaming properties) of PPIs could be further improved after conjugation with polysaccharides. A milk protein such as sodium caseinate (NaCN) was chosen and used as a comparison protein in forming Maillard conjugates. The effects of heating time (0, 1, 2, 3 and 4 hours), protein type (NaCN, S200 or S300), pH (NaCN: pH 7 and 11; S200: pH 7, 9 and 11; S300: pH 3, 4 and 11) or polysaccharide type (MD, pectin and SA) on the formation of Maillard conjugates were investigated using wet-heating method (90℃). The degree of conjugation (DC) and browning index of samples were measured to determine the formation of Maillard conjugates. Results showed that the two PPIs used in this study were quite soluble in water and their water solubility was not highly affected by those factors described in the above (e.g. environmental conditions). The particle size of the PPI-stabilised emulsions was relatively small, making PPIs competitive emulsifiers for food emulsion applications. The foaming properties of the PPIs were also improved after forming Maillard conjugates with different polysaccharides. In conclusion, this study provides useful information for understanding some fundamental physicochemical properties of the two types of commercially available PPIs in relation to their food applications as emulsifying and foaming agents.
The following Figures have been removed for copyright reasons: Figures 2.2, 2.3, 2.5 & 2.6 (=De Oliveira et al., 2016 Figs 1, 2, 6 & 7 respectively), & 2.4 (=Boostani et al., 2017 Fig 1).
Keywords: 300607 Food technology